Eksistensi Lembaga Pengawasan Ombudsman dalam Penyelenggaraan Pelayanan Publik di Daerah - Triono, Agus (Sosiologi: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2015)
Public service is a citizens constitutional right guaranteed by the constitution that must be organized as well as possible and should be monitored. The existence of the Ombudsman oversight agencies that have oversight of the public service to be important in keeping the public administration remains in the observance of law and general principles of good governance. The problem in this research is how the existence of the institution of the Ombudsman in delivering public service in the province of Lampung. Based on research conducted using normative legal research methods and to approach the problem using the statue approach and the conceptual approach, it can be seen that the existence of the Ombudsman oversight agencies are not can be released from the increasing practice of maladministration committed by the state officials both at the central and regional levels. Normatively, the existence of the Ombudsman strengthened by setting it in the Law 37 of 2008 on the Ombudsman of the Republic of Indonesia, Law No. 25 of 2009 on Public Services and Law 23 Year 2014 on Regional Government. In the implementation of its oversight function of public service, Ombudsman in Lampung province has implemented monitoring functions involving various stakeholders, including Provincial Information Commission and Various Institutions/Government Agencies both central and local levels. Nevertheless, Ombudsman in Lampung Province has not optimally performed its function and socialization of the community over its functions oversee public services in the province of Lampung. So expect Ombudsman in Lampung province more socializing existence with all its functions to the broader community and conduct surveillance activities more actively in solving the cases of maladministration that occur without having to wait for a report.Keywords: The existence of the Ombudsman, public service